Development of Aloe Vera-Based Desulfurization Method to Improve The Quality of Sumatra's Coal - Hapsauqi, Iqbal; Desfitri , Erda Rahmilaila; Hanum, Farrah Fadhillah; Setyawan, Martomo (Sains Natural: Journal of Biology and Chemistry, 2024)
Coal is Indonesia's primary energy source, contributing approximately 65.5% to the total electricity production in 2021. The high sulfur gas emissions during the coal combustion have negatively impacted air quality and the surrounding ecosystem. Consequently, researchers have conducted numerous studies on reducing sulfur content in coal. This study specifically explores the impact of adding Aloe vera extract in desulfurization. Aloe vera contains saponin, a surfactant-like compound that can alter the surface properties of minerals in coal, making sulfur particles easier to eliminate. In the experiment, aloe vera extract was applied to coal with variations of 100, 200, and 300 mL. The mixture was stirred using a magnetic stirrer at 100 rpm for one hour. Subsequently, the coal was separated and analyzed for sulfur content, calorific value, and ash content. The research results indicated that adding Aloe vera extract significantly reduces sulfur content in coal, simultaneously improving the overall quality of the coal with a sulfur reduction ranging from 7% to 22%. Moreover, the process reduced the ash content in the coal. By harnessing the potential of Aloe vera as a natural desulfurizing agent, this study presents an innovative and environmentally friendly solution to mitigate hazardous gas emissions during coal combustion.